Exploring the role of learning through play in promoting multimodal learning among children: a pilot study in Chinese first-tier cities - Li, Xiuhan; Zhang, Xiaoman; Zhao, Yongle; Zhang, Lu; Shang, Junjie (Frontiers in Psychology, 2023)
Play is an effective approach to engaging children in learning as an alternative to traditional lecturing. The Learning through Play (LtP) approach involves various modes of learning participation, including multi-sensory participation, interpersonal interaction, and hands-on operation, which can effectively motivate children to learn. This multimodal learning mechanism gives LtP the advantages of openness, diversity, and enjoyment. This study is based on an LtP pilot survey conducted in several first-tier cities of China, which included questionnaires and interviews. Our three research objectives are to present the basic ecology of LtP in China, to explain how LtP supports children’s multimodal learning experiences, and to analyze what affects the development of LtP. We found that LtP has gained great popularity, both conceptually and practically, in China. LtP stakeholders report its behavioral, cognitive, and affective learning effectiveness. The factors influencing the effectiveness of LtP include its inner weaknesses, the subjects involved, the environment, and culture. This study provides a reference for promoting the theory and practice of multimodal learning with a playful approach.